“… I tried to commit suicide…”: Understanding the intersections between mental health, HIV and teenage pregnancy - Hanani Tabana; Takunda Satumba; Diane Cooper; Martina Lembani (PLoS ONE, 2026)
Background Adolescent girls in South Africa face a range of interconnected health challenges, including high rates of unplanned pregnancy and HIV infection, which are compounded by systemic inequities in accessing sufficient health care. These vulnerabilities can significantly affect their mental health and overall well-being. This paper describes adolescent girls’ lived experiences when accessing health care services and how these experiences might be associated with mental health, HIV, and teenage pregnancy in the Western Cape province, South Africa. Methods This qualitative study employed narrative and semi-structured interviews to explore the sexual and reproductive health and mental health well-being of adolescent girls aged 15–19. Participants included adolescent girls in various categories: pregnant, postpartum, living with HIV/AIDS or not, recruited from three youth-friendly primary healthcare facilities using purposive and snowballing sampling methods. A total of 17 adolescents, four healthcare providers, and four parents were interviewed, and a focus group was held, involving six sub-district healthcare program managers. Results The factors contributing to mental health among the adolescents were broadly categorised under five themes: 1) Navigating the impact of unintended pregnancy, 2) Negotiating the home environment and other relationships, 3) Barriers around access to services at the facility level, 4) Community healthcare services, and 5) Improving mental health services. Conclusion This study explored factors that contribute to or hinder the mental well-being of adolescent girls and the barriers to accessing mental health services. Designing tailored approaches to the identified factors and systemic challenges that counter mental distress for this age group can significantly mitigate the impact on their mental health.